Information and communication technologies in teaching and learning english as foreighn language - KOZLAKOVA, Galyna; STRELCHENKO, Oksana (Journal of Education, Technology and Computer Science, 2014)
The integration of ICT in language learning has become essential in today’s teaching-learning environment because the impact of information and communication technology (ICT) on language learning has been recognized globally. Nowadays, there is a great variety of the technology in language teaching and learning: Radio, TV, CD Rom, Computers, C.A.L.L., the Internet, Electronic Dictionary, Email, Blogs and Audio Cassettes, Power Point, Videos, DVD’s or VCD’s. So when the world is fast becoming a global village, the use of modern technological gadgets to improve language learning has become very important as well as in teaching English as EFL. This paper aims at analyzing the necessity of IC technology to language teaching and bringing out the problems faced by its users to make teachers of English aware of the strategies to exercise them in an effective manner.